VD_FINDINFO Jug / 2011 / 124 vom 16. März 2011 - VD Tribunal cantonal (2011)
LOI FÉDÉRALE SUR LES ÉTRANGERS, SÉJOUR ILLÉGAL, PEINE D'ENSEMBLE, RÉVOCATION DU SURSIS | 41 CP, 46 CP, 47 CP, 49 CP, 115 LEtr